Preparation and characterization of bentonite nanocomposites via sol–gel process - Legarto, María Celeste (2019)
Different nanocomposites silica-resin based were prepared and characterized in order to achieve a porous monolith that contains bentonite and allows the flow of aqueous systems. The bentonite used to prepare the nanocomposites was a good adsorbent for various molecules in aqueous media in stirred tank reactor. But the challenge was the obtention of porous bentonite composite columns for industrial applications. The primary composite, silica-resin, was prepared by the sol–gel precursor mixture of the tetraethylorthosilicate (TEOS) and a phenolic resin, made up the gel which is then dried and cured at 180 °C. Bentonite was added to the precursor mixture obtaining the, silica-resin-bentonite composite, and also other potencial adsorbent, carbon, was added obtaining the silica-resin-bentonite-carbon composite. The different composites were mineralogical and structurally evaluated by X-ray diffraction, Infrared spectroscopy with Fourier transform, Differential thermal analyses and thermogravimetric analyses. The textural characterization was performed by Adsorption of nitrogen (Sg-BET), Mercury intrusion porosimetry and Scanning electron microscopy. The comparison of the characteristics and properties between the composites evidenced that the addition of bentonite modify the sol–gel process and interferes in the composite cured process, so that, modify the mesoporosity and macroporosity of the composite. But, there is a maximum clay limit to obtain an homogeneous monolith. The addition of carbon decreases the porosity of the composite to a greater extent when the granulometry is greater.